Pengaturan Status Dan Kedudukan Anak Dari Hasil Perkawinan Campuran Berdasarkan Hukum Di Indonesia - Prasida Alya Putri (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
A wedding is one of the most essential public ceremonies in life. This matters is based on the fact that marriage involves more than simply the bride and husband.; it also involves parents and other families from both sides, as well as some tricky issues. In case with mixed relationships, the issue of the child’s nationality often comes up. Under the old Citizenship Law, which was constructed on the concept of a single nationality, children from mixed marriages were allowed only one nationality; the law dictates that the nationality of the father must be obeyed. This arrangement caused problems down the road of course, the mother would have a hard time finding care for her child if her parents’ marriage broke up. However, considering that Law Number 12 of 2006 concerning Citizenship has been in effect. Mixed-marriage kids have a variety of options. Due to the assurance of their status, they can apply to become citizens of the Republic of Indonesia after they turn 18 or are legally married. When a child turns 18 or marries, they must choose a nationality and they can no longer have dual citizenship.